2017
DOI: 10.1248/yakushi.16-00222
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Preventing Local Venous Pain by Dacarbazine

Abstract: Local venous pain caused by dacarbazine (DTIC) injection is due to its photodegradation product 5-diazoimidazole-4-carboxamide (Diazo-IC). The production of Diazo-IC can be decreased by protecting the drug from light. Furthermore, the production of Diazo-IC reportedly increases with time; however, there are no studies reporting the association between the injection preparation time and local venous pain caused by the DTIC injection. We evaluated the e‹cacy of the following: (1) method used to shorten the injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Recent reports have demonstrated that light shielding during the infusion process reduced the photo-degradation of DTIC. 3,6,9) The infusion process of DTIC requires 2-3 h, while the dissolving and diluting processes require a total of 10 min. A short duration of light exposure most likely does not increase the production of Diazo-IC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have demonstrated that light shielding during the infusion process reduced the photo-degradation of DTIC. 3,6,9) The infusion process of DTIC requires 2-3 h, while the dissolving and diluting processes require a total of 10 min. A short duration of light exposure most likely does not increase the production of Diazo-IC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the procedure for reducing the pain reaction during peripheral intravenous infusion of DTIC. [4][5][6][7] The dissolving solution selected and the adjustment of its pH were found to affect the photo-degradation. 8) Light shielding infusion bags with a light-blocking sheet reduced the generation of Diazo-IC during peripheral intravenous infusion.…”
Section: Introductionmentioning
confidence: 99%
“…However, the poor solubility and short half-life of DTIC in water further limit its application in combination therapy. Therefore, a promising strategy to overcome these limitations is to encapsulate DTIC in nanocarriers for targeted delivery to tumor cells . Many approaches have been developed for the treatment of malignant melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a promising strategy to overcome these limitations is to encapsulate DTIC in nanocarriers for targeted delivery to tumor cells. 9 Many approaches have been developed for the treatment of malignant melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, usage of DC in the treatment of melanoma is restricted due to its various disadvantages. First problem with DC is it is administered in blood by intravenous route only which is a painful route of administration and usually patient avoids this due to incompliance 18 . Second is the absorption rate of DZ is in general incomplete, slow and erratic because of its poor water solubility 19 .…”
Section: Introductionmentioning
confidence: 99%